Arrest 1848: Manuscript by Václav Krolmus on the Invitation to Preach a Sermon at White Mountain on June 9, 1848 with an Abstract of the Sermon He Preached - Šiková, Olga (Lidé města, 2013)
This historical source presents the manuscript of the sermon delivered in June 1848 by Václav Krolmus. The transliterated personal document reflects the atmosphere of this revolutionary year from the perspective of a patriotic Czech Catholic priest, politician, writer, archaeologist and ethnographer. The manuscript opens the intellectual world of a person who was actively involved in the historical events that supported the development of future Czech society, and demonstrates his attitudes and opinions. The publication includes Krolmus's biography, as well a description and analysis of the historical source.